(untitled) (Experimental biology, 2015)
Prognose of the specter of biological activity of complex on the base of piridoksin, glicine and iron was conducted with the help of Pass (Prediction of Activity Spectra for Substances) computer program. The given computer program showed great for casting prognosal ability which was confirmed by experiments.